The soft computing FFNN method for adjusting heteroscedasticity on the time series model of currency exchange rate - Devianto, Dodi; Yollanda, Mutia; Maiyastri, Maiyastri; Yanuar, Ferra (Frontiers in Applied Mathematics and Statistics, 2023)
Time series models on financial data often have problems with the stationary assumption of variance on the residuals. It is well known as the heteroscedasticity effect. The heteroscedasticity effect contained in the basic classical time series model of ARIMA can adjust its residuals as the variance model by using GARCH. In improving the model accuracy and overcoming the heteroscedasticity problems, it is proposed a combination model of Autoregressive Integrated Moving Average (ARIMA) and Feed-Forward Neural Network (FFNN), namely ARIMA-FFNN. The model is built by applying the soft computing method of FFNN to replace the variance model. This soft computing approach is one of the numerical methods that can not be only applied in the theoretical subject but also in data processing. In this research, the accuracy of the time series model using the case study of the exchange rate United States dollar-Indonesia rupiah with a monthly period from January 2001 to May 2021 shows that the best accuracy of the possible models is the model of ARIMA-FFNN, which applies soft computing to obtain the optimal fitted parameters precisely. This result indicates that the ARIMA-FFNN model is better used to approach this exchange rate than the rest model of ARIMA-GARCH and ARIMA-GARCH-FFNN.